Unveiling the UHR threshold in American adult: a new biomarker for early diabetes detection from NHANES study - Chao Yu; Zuting Liu; Jian Zhong; Xingyu Liu; Jiali Mo; Jie Kuang (BMC Endocrine Disorders)
Abstract Background and aims This study examines the association between the serum uric acid high-density lipoprotein cholesterol ratio (UHR) biomarker and the risk of prediabetes and diabetes, a relationship that remains under-researched, to provide insights for diabetes prevention. Methods and results This study utilized data from 13,975 American participants in the National Health and Nutrition Examination Survey (2011–2018). Logistic regression models, restricted cubic splines (RCS) analysis and subgroup analyses were employed to examine the association between UHR and prediabetes/diabetes. The median UHR was 10.4%, with 6,382 (45.7%) cases of prediabetes and diabetes detected. A higher UHR was associated with an increased risk of prediabetes and diabetes, showing a 39% increased risk per standard deviation increment (OR: 1.39; 95% CI: 1.33,1.46). Consistent results were observed when UHR was categorized. Participants in the highest UHR quartile exhibited a significantly higher risk of prediabetes/diabetes than those in the lowest quartile (OR: 2.63, 95% CI: 2.30,3.01). The RCS analysis revealed a nonlinear association, with a threshold value of 12.50%. Below this threshold, higher UHR was significantly associated with prediabetes/diabetes (OR: 1.17, 95% CI: 1.15,1.19), while above this threshold, the association was not significant. Subgroup analyses highlighted a marked gender disparity, with women exhibiting a stronger association. Conclusion This research found a positive link between UHR and prediabetes and diabetes prevalence, with a nonlinear relationship noted. A significant association was observed below a UHR threshold of 12.50%, especially in females.